Analisis Perlakuan Akuntansi Aktiva Tetap Pada Koperasi Kredit Swastiastu Singaraja Kabupaten Buleleng - Ni Luh Gede Erni Sulindawati; dewa ayu tiara carma putri (Vokasi : Jurnal Riset Akuntansi, 2022)
This study aims to determine the accounting treatment of fixed assets in the Swastiastu Singaraja Credit Cooperative, Buleleng Regency. The data analysis technique in this study used comparative descriptive analysis, the data collection methods used were interviews, documentation and observation. The results showed that (1) the accounting treatment applied to the Singaraja Swastiastu Credit Cooperative, Buleleng Regency, had applied accounting treatment in accordance with Financial Accounting Standards such as making a list of fixed assets, journaling and calculating the depreciation of fixed assets. (2) The accounting treatment of fixed assets at the Swastiastu Credit Cooperative after being depreciated in accordance with Financial Accounting Standards with the straight-line method, the book value becomes smaller than the previous book value. (3) The effect of accounting for fixed assets on the financial statements after being depreciated by Financial Accounting Standards affects the book value in which the book value of fixed assets decreases